2012
DOI: 10.1021/ma302246u
|View full text |Cite
|
Sign up to set email alerts
|

Living Anionic Polymerization of 1,4-Divinylbenzene and Its Isomers

Abstract: The anionic polymerization of 1,4-divinylbenzene (1) and its ortho (2) and meta isomers (3) were studied under a variety of conditions. One of the two vinyl groups of 1 was selectively and exclusively polymerized in a living manner by the addition of a suitable additive under the conditions of −78 °C for 1 min and −95 °C for 30 min. Under such conditions, the unwanted addition reaction of the chain-end anion to the pendant vinyl group was almost suppressed and soluble polymers with predictable molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 36 publications
(41 reference statements)
4
54
0
Order By: Relevance
“…m. (m-DVB). 37 ) and/or shorter distance between the two vinyl groups. The 1 H NMR analysis of the star-shaped polymer and the residual arm, which were separated via reprecipitation in n-hexane, indicated that the unreacted vinyl groups remained in the star-shaped polymer and that the ω-end functionality of the arm polymer was low (Supplementary Figure S5).…”
Section: Cationic Polymerization Of St and Its Derivativesmentioning
confidence: 99%
“…m. (m-DVB). 37 ) and/or shorter distance between the two vinyl groups. The 1 H NMR analysis of the star-shaped polymer and the residual arm, which were separated via reprecipitation in n-hexane, indicated that the unreacted vinyl groups remained in the star-shaped polymer and that the ω-end functionality of the arm polymer was low (Supplementary Figure S5).…”
Section: Cationic Polymerization Of St and Its Derivativesmentioning
confidence: 99%
“…SEC profiles of polymers in THF; a) poly( 2 ) obtained with K‐Naph after 1 min (run 9), b) poly( 2 ) with αMSLi/ t BuOK after 1 h (run 13), and c) poly( o ‐DVB) prepared by the anionic polymerization of o ‐DVB under the same condition as run 13 …”
Section: Resultsmentioning
confidence: 93%
“…The anionic polymerizations of DVB isomers, o ‐DVB and m ‐DVB, were also attempted with αMSLi/ t BuOK . The polymerization of o ‐DVB was highly controlled under the identical condition for p ‐DVB described above, giving a soluble polymer with well‐controlled chain structures.…”
Section: Introductionmentioning
confidence: 99%
“…Although several other potassium alkoxides were found to be also effective in the polymerization of p-DVB, KOBu t was always used throughout this study because it was one of the best additives. 11 The polymerization of p-DIPB readily proceeded in THF at −78°C to afford a soluble polymer in 95% yield after 48 h. The dark red color, characteristic of the living styryl anion derived from p-DIPB, remained unchanged during the polymerization. The resulting polymer shows a sharp SEC peak (M w /M n = 1.03) without any higher-molecular-weight portion ( Figure 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, the less stabilized and more reactive chain-end anion may facilitate the addition reaction leading to the chainbranching, like m-DVB previously reported. 11 The polymerization of o-DIPB was also carried out under the identical conditions. In this case, only a small amount of oligomer (average molecular weight = ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%